1979
DOI: 10.1159/000241188
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nicotine on the Development of Fetal and Suckling Rats

Abstract: Nicotine, administered at a dose of 100 μg/kg/day from day 14 of gestation, did not affect maternal food intake, weight gain, length of gestation, litter size or fetal development; however, a daily dose of 1 mg/kg led to smaller litter size and higher incidence of stillbirth. Continued maternal administration of nicotine (100 μg/kg/day) until 12 days postpartum did not affect newborn growth (body weight and length and size of heart and lung) during the first week after birth; during the second week, however, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

1981
1981
2014
2014

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…Pa ) was administered via an osmotic mini pump (Alza Research Company, Palo Alto. Calif.) [18]. On day 16 of gestation, the experimental animals were anesthetized with ether and the pumps were implanted suprascapularly beneath the subcutaneous tissue, where they remained until sacrifice.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Pa ) was administered via an osmotic mini pump (Alza Research Company, Palo Alto. Calif.) [18]. On day 16 of gestation, the experimental animals were anesthetized with ether and the pumps were implanted suprascapularly beneath the subcutaneous tissue, where they remained until sacrifice.…”
Section: Methodsmentioning
confidence: 99%
“…The uteri were clamped in situ, resected and removed to Petri dishes containing cold 0.85% saline [18]. The fetuses were delivered and weighed individually.…”
Section: Preparation O F Tissues For Lipoprotein Lipase Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…19 Newborn rats given nicotine injections during gestation and lactation exhibited reduced weight gain and linear growth at the end of the first half of lactation. 20 In contrast, newborn rats given nicotine during gestation, but not during lactation exhibited reduced birth weight, but with no significant difference in weight at weaning after 21 days. 21 Studies with humans have shown that, although smoking during pregnancy is associated with newborn infants whose weights are lower when delivered, after birth, these children tend to catch up with the ideal growth curve.…”
Section: Discussionmentioning
confidence: 92%
“…Table 2 summarizes the results of 56 studies that reported the effects of developmental nicotine exposure on birth weights and somatic development, as well as maternal and gestational variables (all the studies had "body weight" in the abstract or as a key term). Studies that report birth weight after prenatal or pre-and postnatal exposure to nicotine are equally likely to show no differences (Ajarem and Ahmad 1998;Bertolini et al • 1982;Eppolito and Smith 2006;Eppolito et al 2010;Franke et al 2007;Fung 1988;Hamosh et al 1979;Levin 1993;Navarro et al 1989a;Paulson et al 1993;Paz et al 2006;Peters 1984;Peters and Ngan 1982;Peters and Tang 1982;Richardson and Tizabi 1994;Romero and Chen 2004;Segarra and Strand 1989;Sobrian et al 1995Sobrian et al , 2003Somm et al 2008) or lower birth weight (Carmines et al 2003;Cutler et al • 1996;Gaworski et al 2004;Holloway et al 2005;Johns et al 1982;LeSage et al 2006;Martin and Becker 1971;Martin et al 1976;Navarro et al 1989a;Newman et al 1999;Paulson et al 1994;Peters 1984;Peters and Tang 1982;Roy and Sabherwal 1994;Schneider et al 2010;Shacka et al 19...…”
Section: Birth Weightmentioning
confidence: 99%